An Exploration into the Interrelation between EFL Learners’ Self-Regulated Learning, Self-Determined Motivation, and Academic Persistence - Mohammad Sharafi (Faculty of Education and Teacher Training of UIN Palopo, 2024)
Self-determined motivation, self-regulated learning, and academic persistence are recognized as pivotal non-cognitive factors shaping students’ academic advancement (Watts-Martinez, 2015). The increasing public interest in higher education outcomes propels researchers to explore the factors contributing to persistence and successful college completion. Motivation may function as a mediating factor between self-regulated learning and academic persistence. Despite their significance, the interrelation between these factors, particularly in the context of learning English as a foreign language, has not yet been thoroughly examined. This review delves into the theoretical foundations of this interrelation, shedding light on its importance and potential impacts, especially in non-English-speaking contexts such as Iran. The literature suggests that understanding how orientations of self-determined motivation, whether intrinsic or extrinsic, influence EFL students’ academic persistence is crucial. This gains particular significance in the context of English language education, especially at the tertiary level, warranting further analysis.